THE EFFECT OF FINANCING SOURCES AND LIQUIDITY ON FIRM VALUE: (Case Study on Plantation and Food Crop Sub-Industry Companies Listed on the Indonesia Stock Exchange for the 2020-2024 Period) - Resa Rusmana Saputri; Herlina Rasjid; Meriyana Franssisca Dungga (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of financing sources and liquidity on firm value, with a case study on plantation and food crop sub-industry companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The research method employs a quantitative approach using secondary data obtained from annual financial reports. The population includes all plantation and food crop companies listed on the IDX. The sample was selected using a purposive sampling method, resulting in 14 companies with 70 observational units (5 years x 14 companies). Data analysis was performed using the Statistical Product and Service Solution (SPSS) method. The results indicate that both financing sources, proxied by the Long-term Debt to Equity Ratio (LTDER), and liquidity, proxied by the Current Ratio (CR), have a positive and significant effect on firm value, as measured by the Price to Book Value (PBV). Simultaneously, both variables also significantly influence firm value.